Soot Oxidation Activity of Redox and Non-Redox Metal Oxides Synthesised by EDTA-Citrate Method - Anantharaman, Anjana P.; Dasari, Hari Prasad; Lee, Jong-Ho; Dasari, Harshini; Babu, G. Uday Bhaskar (SPRINGER, 2017)
In the present study, redox (CeO2, SnO2, Pr6O11 and Mn3O4) and non-redox (Gd2O3, La2O3 ZrO2 and HfO2) metal oxides were successfully synthesised using the EDTA-citrate complexing method and tested for soot oxidation activity. The characterization of the metal oxides is carried out using FTIR, XRD, BET surface area, pore volume analyser, SEM and TEM. The redox nature and metal-oxygen bond information of the metal oxides are obtained from XPS analysis. In redox metal oxides, three critical parameters [lattice oxygen binding energy, reduction temperature and Delta r (ionic size difference of the corresponding metal oxide oxidation states)] govern the soot oxidation activity. Among the redox metal oxide samples, Mn3O4 and Pr6O11 samples showed lower binding energy for oxygen (O-beta-529.4, 528.9 eV respectively), lower reduction temperature (T-alpha-317 and 512 A degrees C respectively) and have smaller Delta r value (9 pm and 17 pm respectively). Thus, displayed a better soot oxidation activity (T-50 = 484 and 482 A degrees C respectively) than compared to other redox metal oxides. Among the non-redox metal oxides, HfO2 sample displayed higher BET surface area (21.06 m(2)/g), lattice strain (0.0157), smaller ionic radius (58.2 pm) and higher relative surface oxygen ratio (58%) and thus resulted in a significantly better soot oxidation activity (T-50 = 483 A degrees C) than compared to other non-redox metal oxides. [GRAPHICS]
Keywords: ZIRCONIA SOLID-SOLUTIONS; CERIA-ZIRCONIA; CATALYTIC-ACTIVITY; MANGANESE OXIDE; CO OXIDATION; DIESEL SOOT; SURFACE; CEO2; NANOPARTICLES; COMBUSTION